Association between the organoleptic scores, oral condition and salivary β‐galactosidases in children affected by halitosis. Issue 3 (28th May 2014) - Petrini, M; Costacurta, M; Ferrante, M; Trentini, P; Docimo, R; Spoto, G
Abstract Objectives The goal of this work is to evaluate the association between organoleptic scores, oral condition and salivary β‐galactosidases, to facilitate the differential diagnosis of halitosis in children. Methods Fifty systemically healthy children with a primary complaint of oral malodour were included in this cross‐sectional study. The organoleptic evaluation was carried out by two judges, evaluating the intensity of malodour of the air exhaled 5 s through the mouth of the patients, at a distance of approximately 10 cm from their noses; the level of salivary β‐galactosidases was quantified spectrophotometrically after a chromatic reaction between a salivary sample of each patient and a specific chromatic substrate of the enzyme. Clinical conditions, such as visible plaque and gingival bleeding index, tongue coating score, localized food stagnation and other oral parameters, were evaluated by qualified dentists through an oral check‐up. Results The β‐galactosidase level was significantly related to the organoleptic scores and clinical parameters, such as the tongue coating score and the visible plaque index. Stratifying results with respect to the different phase of the day at which parents complained halitosis in their children, statistical analysis showed that the organoleptic scores and the level of β‐galactosidases were significantly higher in children who suffered of halitosis during the whole day, A = 40%, with respect to those without this problem, N = 20% (P = 0.001 and P = 0.006, respectively). Conclusions Certain oral parameters such as halitosis during the whole day, high tongue coating score and high visible plaque index were particularly associated with an increase in the salivary β‐galactosidase level.